2022
DOI: 10.1002/ajh.26628
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific T‐cell engagers for treatment of multiple myeloma

Abstract: Bispecific T cell engagers (TCE) derive from monoclonal antibodies and concomitantly engage a target on the surface of cancer cell and CD3 on the surface of T-cells. TCEs promote T cell activation and lysis of tumor cells. Most TCEs in development for multiple myeloma (MM) target the B cell maturation antigen (BCMA) and differ among themselves in structure, pharmacokinetics, route and schedule of administration. CD3/BCMA TCEs produce response in $60% of patients treated in phase 1 trials. TCEs are also in deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…At the beginning of this century, the average overall survival of MM patients was about 3 years, when the main therapeutic agents were bortezomib, lenalidomide and thalidomide ( 26 ). The subsequent application of treatments including daratumumab, chimeric antigen receptor T cells, autologous hematopoietic stem cell transplantation, and bispecific T-cell engagers has greatly improved the survival of MM patients ( 27 , 28 , 29 ). However, regardless of the improvement in treatment modalities, MM is still an incurable tumor and it is inevitable that patients will experience recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of this century, the average overall survival of MM patients was about 3 years, when the main therapeutic agents were bortezomib, lenalidomide and thalidomide ( 26 ). The subsequent application of treatments including daratumumab, chimeric antigen receptor T cells, autologous hematopoietic stem cell transplantation, and bispecific T-cell engagers has greatly improved the survival of MM patients ( 27 , 28 , 29 ). However, regardless of the improvement in treatment modalities, MM is still an incurable tumor and it is inevitable that patients will experience recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The two common antigens involved are CD3 and CD16, and BCMA is the target of MM plasma cells. Many studies with BITEs utilizing BCMA showed great efficacy with moderate toxicity, such as CRS (cytokine release syndrome) and associated neurotoxicity syndrome (ICANS) [ 80 - 82 ] .…”
Section: Bcma-targeted Treatment In Multiple Myelomamentioning
confidence: 99%
“…Similar to CAR T-cells, the dual binding of TEC results in the activation of the endogenous immune cells triggering cytokine release surge [5]. Apart from BCMA, other molecular targets on PCs currently assessed include the GPRC5D and FcRH5 [14].…”
Section: Mechanism Of Actionmentioning
confidence: 99%